RELATIONSHIP CURRICULUM DIDACTICS: I SPIN DRIVER OF THE DAILY PLANATION OF THE CLASS - Pino Batista, Manuel Guillermo; Hernández Barrenechea, Amado Lorenzo; Hernández Fuentes, Marisel (Atenas, 2015)
In the article the existent relationship is expressed between the curriculum and the didactics. When valuing the professional problems and the general objectives that you/they appear in the professional’s pattern aspirations they are appreciated the teaching-learning process should be developed in the careers of Mathematics-physics, Biology-chemistry and Biology-geography showing before the relationship of how mentioned. The class, from the didactic point of view, is the fundamental form of organization of the process, to achieve the quality of this, it is important to carry out a good planation of the same one keeping in mind the demands of the curriculum of the career.